Assistance in Enhancing Credit Risk Analysis Competence for Account Officers at PT. BPRS Bangun Drajat Warga Yogyakarta - Gita Danupranata; Rijal Yaya; Muhammad Khaeruddin Hamsin; Riduwan Riduwan (Journal of Islamic Economy and Community Engagement, 2026)
Enhancing credit risk analysis competence for Account Officers (AOs) is crucial for maintaining financing portfolio quality and minimizing problematic financing risks. This service aims to identify competency needs, evaluate AOs’ analytical skills, and develop effective strategies through training and decision support system enhancements.   The service method uses classical training and online/offline consultation. Results show core competencies include character, capacity, capital, collateral, and condition of economy (5C) analysis, prudential principles, and sharia compliance. Improved competence significantly impacts risk assessment accuracy, financing process efficiency, and portfolio quality. This service recommends a sustainable development model based on structured learning, on-the-job coaching, and leveraging analytic technology to support objective credit assessment and risk control.